The characterization of DNAJC3: elucidating the function of the TPR domains - Mutsvunguma, Lorraine Zvichapera (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2014)
DNAJC3 is a novel member of the DNAJ family with two domains linked to co-chaperone functions, namely the tetratricopeptide repeat (TPR) and J domain. Out of the two domains, the TPR domains are the least characterized. Therefore, the aim of this study was to characterize and elucidate additional functions of DNAJC3 TPR domains through in silico, in vitro and ex vivo approaches. Through multiple sequence and structural alignment as well as electrostatic potential analysis, DNAJC3 TPR domain were found to be most similar to TPR-containing proteins with Hsp90 or Hsp70 independent functions. In vitro pull down assays illustrated that DNAJC3 TPR domains did not interact with either cytosolic Hsp90 and Hsp70 or Grp78 and Grp94 directly, however a potential indirect interaction with Grp94 and Hsp90 was observed in mammalian lysates, via pull down assays; suggesting the formation of a complex between the proteins mediated by a specific substrate. DNAJC3 TPR domains were found to bind indiscriminately to both native and heat denatured substrates in a dose dependent manner. DNAJC3 TPR domains bound to Î²-galactosidase with greater affinity than malate dehydrogenase (MDH), suggesting that DNAJC3 TPR domains might exhibit substrate specificity that has not been reported before. Preliminary ex vivo analysis of DNAJC3 in mammalian cells showed that induced stress conditions did not alter the cytosolic or endoplasmic reticulum (ER) localization, or levels of DNAJC3 protein, suggesting that the protein is not stress inducible. However, protein levels of DNAJC3 were dramatically reduced by Hsp90 inhibitor novobiocin at 500 Î¼M. Transient knockdown DNAJC3 did not change the protein levels of either Grp78 or Grp94, but decreased the protein levels of Hsp70/Hsp90 organizing protein HOP. On the other hand, protein levels of DNAJC3 were increased in HOP depleted cells. In conclusion, this study was the first to experimentally demonstrate that DNAJC3 TPR domains do not interact directly with Hsp90, Hsp70, Grp78 or Grp94, and therefore DNAJC3 is unlikely to participate in traditional co-chaperone interactions with those proteins via its TPR domain. However, the J domain is known to interact with Grp78. The discovery that DNAJC3 TPR domains resemble that of TPR-containing proteins with functions independent of Hsp90 or Hsp70 suggests that DNAJC3 might link the Hsp70/Grp78 chaperone machinery to non co-chaperone related functions, which requires further analysis.
Keywords: Uncatalogued